Legal Protection in Consumer Dispute Resolution: Independence of the Financial Services Authority (OJK) - Abdillah, Riad; Sjaifurrachman, Sjaifurrachman; Prakoso, Abintoro; Dwi Hastri, Evi (International Asia Of Law and Money Laundering (IAML), 2024)
The progress of the national economy is influenced by financial services. The Financial Services Authority (OJK) as an independent institution that is responsible and plays an important role in supervising and regulating management in the financial services sector, is committed to providing legal protection guarantees for consumer rights. The normative legal research method using a statutory approach and this concept approach shows the results that the Financial Services Authority (OJK) has used the concept of Alternative Dispute Resolution (ADR) as part of pseudo/quasi by establishing an Alternative Dispute Resolution Institution based on OJK Regulation Number 61/POJK.07/2020 of 2020 concerning Alternative Dispute Resolution Institutions in the Financial Services Sector as a follow-up step taken to provide legal protection to consumers in the financial services sector in regulating and resolving disputes or complaints. In addition, the independence of the Financial Services Authority (OJK) has guaranteed in protecting consumers in the financial services sector with the issuance of OJK Regulation Number 6/POJK.07/2022 of 2022 concerning Consumer and Public Protection in the Financial Services Sector.